The The Effect of the Talking Stick Cooperative Learning Model on Biology Learning Outcomes at SMA Negeri 1 Waingapu (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2023)
This study aims to determine the effect of the Talking Stick Cooperative Learning Model on Biology Learning Outcomes at SMA Negeri 1 Waingapu. This type of research is a quasi-experimental design using a nonequivalent control group design with a quantitative approach. Sampling using purposive sampling. The population in this study were students of class XI MIPA in the odd semester of the 2022/2023 academic year. The sample of this study was 37 students of class XI MIPA 1 as the control class and 37 students of XI MIPA 5 as the experimental class. The results of the descriptive analysis obtained showed that the average pre-test and post-test scores for the experimental class were 61.76